2011
DOI: 10.1016/j.envpol.2011.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of clear-cutting and selective cutting on soil methane fluxes in a temperate spruce forest in southern Germany

Abstract: a b s t r a c tBased on multi-year measurements of CH 4 exchange in sub-daily resolution we show that clear-cutting of a forest in Southern Germany increased soil temperature and moisture and decreased CH 4 uptake. CH 4 uptake in the first year after clear-cutting (À4.) was three times lower than during the pre-harvest period (À14.2 AE 1.3 mg C m À2 h À1 ). In contrast, selective cutting did not significantly reduce CH 4 uptake. Annual mean uptake rates were À1.18 kg C ha À1 yr À1 (spruce control), À1.16 kg C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 49 publications
4
24
0
1
Order By: Relevance
“…As it was verified that orchards had been established for many years in subtropical, China consumed atmospheric CH 4 at much higher rates because of less soil disturbance (Iqbal et al 2009). Similarly, in a temperate spruce forest, Wu et al (2011) found that the reduced soil CH 4 oxidation capacity due to land use conversion could last for a decade or even longer. Thus, long-term continuous measurements over several years are needed to understand the dynamics of GHG fluxes during different stages after land use conversion.…”
Section: Discussionmentioning
confidence: 93%
“…As it was verified that orchards had been established for many years in subtropical, China consumed atmospheric CH 4 at much higher rates because of less soil disturbance (Iqbal et al 2009). Similarly, in a temperate spruce forest, Wu et al (2011) found that the reduced soil CH 4 oxidation capacity due to land use conversion could last for a decade or even longer. Thus, long-term continuous measurements over several years are needed to understand the dynamics of GHG fluxes during different stages after land use conversion.…”
Section: Discussionmentioning
confidence: 93%
“…An incubation study with soils from various land use types by Wu et al (2010a) revealed that soils consumed much less or even emitted CH 4 during freezing. In addition to affecting microbial activity (Ding and Cai 2007), soil freezing may also limit the transport of gases by creating diffusion barriers (Borken et al 2006;Wu et al 2011). The enhanced CH 4 consumption during thawing might be partly ascribed to increased methanotrophy and reduced methanogenesis at low temperatures (Ding and Cai 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Another study in a temperate forest actually showed an increased CH 4 uptake after thinning, as opposed to a decrease at two adjacent clear-cut areas (Bradford et al, 2000). Some studies found no significant changes in CH 4 exchange after thinning (Wu et al, 2011;Sullivan et al, 2008).…”
Section: E Sundqvist Et Al: Short-term Effects Of Thinning Clear-cmentioning
confidence: 99%
“…However, several studies reported that clear-cutting led to reduced CH 4 uptake, possibly due to increased soil moisture (Wu et al, 2011), increased nitrogen availability (Steudler et al, 1991;Bradford et al, 2000), changes in pH (Bradford et al, 2000) and erosion (Kagotani et al, 2001). A shift from soil CH 4 sink to soil CH 4 source has been reported due to a rise in water table depth combined with increases in substrate availability (Zerva and Mencuccini, 2005) and due to increases in soil moisture (Castro et al, 2000).…”
Section: E Sundqvist Et Al: Short-term Effects Of Thinning Clear-cmentioning
confidence: 99%